Case of mistaken identity: resolving the taxonomy between Trioza eugeniae Froggatt and T. adventicia Tuthill (Psylloidea: Triozidae). Issue 3 (23rd June 2020) - Taylor, Gary S.; Martoni, Francesco
Abstract: The 'Eugenia psyllid' or 'Lilly pilly psyllid', widely recognized in Australia and in the USA as Trioza eugeniae Froggatt (Hemiptera: Triozidae), is not T. eugeniae, but rather T. adventicia Tuthill. In this study we assessed morphological comparisons of materials from throughout the native and introduced ranges and re-examined original descriptions of both taxa, together with Froggatt's type specimens of T. eugeniae . Furthermore, through DNA barcoding analyses, we confirmed the validity of both T. adventicia and T. eugeniae as separate species. We re-described both species to include additional characters not previously included and designated a lectotype for T. eugeniae . T. eugeniae has smaller fore wings that are slightly more elongate. These lack infuscation around veins R and R1, vein Rs is relatively longer, meeting the costa closer to the wing apex; with certain veins bearing long, fine divergent setae, a character not previously described. It has consistently three inner and one outer metatibial spurs. The male parameres appear narrowly pyriform with a weak dorsolateral lobe and weakly sclerotized apices. T. adventicia has larger fore wings that are slightly more ovate with dark infuscation around veins R and R1 ; vein Rs is relatively shorter, meeting the costa further from the wing apex, with veins lacking long, fine divergent setae. The usual configuration of two inner and one outer metatibial spurs, previously used to separate the two species, appears inconsistent. The male parameres appear a little more broadly pyriform with slightly more sclerotized apices. T. eugeniae refers to a distinct species which has a restricted distribution only in its native range in southern subcoastal New South Wales, Australia. T. adventicia refers to a separate species, with a natural distribution in eastern subcoastal Australia, but has been introduced widely in southern Australia, to New Zealand and the USA. This study elucidates a long history of misidentification of T. eugeniae in the nursery industry and in almost 30 years of literature on its biological control in the USA. Regardless, the biological control program, unknowingly, targeted the correct species of psyllid, T. adventicia, in its foreign exploration and importation of the appropriate parasitoid as a biocontrol agent in the USA. Despite being firmly entrenched in both the nursery trade and scientific literature, the name T. eugeniae is misapplied. While the acceptance of the valid name, T. adventicia, might be regarded as both problematic and protracted, this is the correct taxonomical attribution.